2019
DOI: 10.5334/ijic.4643
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Acute Units as Part of the Clinical Pathway for Older Patients

Abstract: Introduction:Since 2016, Norwegian municipalities have been obliged to provide municipal acute 24-hour services representing a service before or instead of hospital treatment. This study explores two municipal acute units (MAUs) as part of the clinical pathway for older patients.Methods:Patients and healthcare providers from MAUs, purchaser offices, home-based nursing, and physicians were interviewed. Interview transcripts were analysed using systematic text condensation.Results:The collaboration between the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In addition, ‘the loop’ was requested by physicians and nurses at the MAWs. In contrast, a recent study found that PCPs felt that the diagnostic loop was an inappropriate use of time and resources [ 31 ]. Managing diagnostic uncertainty has been reported as a recurring challenge for physicians [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, ‘the loop’ was requested by physicians and nurses at the MAWs. In contrast, a recent study found that PCPs felt that the diagnostic loop was an inappropriate use of time and resources [ 31 ]. Managing diagnostic uncertainty has been reported as a recurring challenge for physicians [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the PCPs seemed to lack insight into the nurses’ educational backgrounds and experience. Johannessen and Steihaug found that a lack of medical expertise was perceived as stressful and unsafe for nurses working in MAWs [ 31 ]. A Cochrane review indicated that nurse-led health services provide similar or better health outcomes, such as reduced mortality or reduced symptom burden for patients, than physician-led health services [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Norway, they have municipal acute units that are different from the Danish model. A Norwegian study found that the cross-collaboration was challenging because healthcare professionals had trouble with sharing information across sectors and different perceptions of which patients were candidates to stay at these units [ 29 ]. This study found the opposite to be true because the collaboration was going well, the main group of patients seemed to be clear and information exchange protocols were clear.…”
Section: Discussionmentioning
confidence: 99%
“…For future research, changes in the acute care pathways of older patients are needed to improve their care by providing alternatives to ED presentations, such as high urgency outpatient department 24 or the introduction of advanced care planning. 25 Furthermore, it would be interesting to see whether some causes are tied to perceived preventability more than others and to include other healthcare workers in the analysis of root causes.…”
Section: Discussionmentioning
confidence: 99%